Environmental Protection and Sustainable Development in the European Union: Evolution, Governance and Implications for Competitiveness - Bongardt, Annette (2012)
This article considers how the EU governance set-up envolved with respect to environmental protection and sustainable development. It aims at evaluating the EU´s progress towards creating  the basis for a competitive, low-carbon, European economy (a kind of EU industrial strategy) and sustainable production and consumption patterns. The article concludes that environmental and energie policies have become increasingly Europeanized and come under the single market and competitiveness rationale. It puts forward that the shift to a low-carbon economy is associated with important economic benefits, whereas economic costs appear overrated. However, shortcomings in EU governance sit uneasily with a more coherent approach to sustainable development. Resumo Este artigo analisa como a governança da UE se envolveu na proteção ambiental e no desenvolvimento sustentável. Destina-se a avaliar os progressos da UE no sentido de criar as bases para uma economia europeia competitiva e hipocarbónica (uma espécie de estratégia industrial da UE) e para padrões sustentáveis de produção e consumo. O artigo conclui que as políticas ambientais e energéticas se tornaram cada vez mais europeizadas e estão sob o lema do mercado único e da competitividade. O artigo defende que a mudança para uma economia de baixo carbono está associada a importantes benefícios económicos, enquanto os custos económicos parecem sobrestimados. No entanto, as deficiências na governação da UE assemelham-se desconfortavelmente com uma abordagem mais coerente do desenvolvimento sustentável.